Comparison of sodium and KCl-MgCl2 as heat transfer fluids in CSP solar tower with sCO2 power cycles. (1st March 2018) - Polimeni, Simone; Binotti, Marco; Moretti, Luca; Manzolini, Giampaolo
Highlights: The use of different sCO2 power cycles coupled with a solar tower system is studied. Sodium and KCl-MgCl2 receivers performance are compared with a simplified model. Two different solar field are designed for Sodium and KCl-MgCl2 receivers. Optical, thermal and power cycle performances are evaluated with dedicated tools. The nominal and yearly solar-to-electric efficiency are computed for two sites. Abstract: This work assesses the performance of a solar tower power plant based on liquid sodium as heat transfer fluid and supercritical CO2 cycles. The adoption of liquid sodium as heat transfer fluid allows maximum temperatures up to 750 °C and higher heat fluxes on the receiver with respect to molten salts (both Solar Salts and KCl-MgCl2 ) also considered as reference. The assessment is carried out through detailed modeling of the solar to electricity conversion processes accounting for detail optical, thermal and power block models. Results at design conditions show that plants using sodium as HTF in the receiver can achieve overall efficiency above 25%, whereas the use of Solar Salts at 565 °C and KCl-MgCl2 at 750 °C reach 21.5% and 24% respectively. The higher efficiency is consequence of the higher thermal efficiency of sodium which is achieved increasing the concentration ratio. Considering a yearly analysis, the overall efficiency of sodium reduces to 20.5% and 19.3% in Seville and Las Vegas respectively which is 7–9% higher than using KCl-MgCl2 and 11% with respect to Solar Salts. Outcomes of this work are the importance of (i) coupling higher temperatures with higher allowable fluxes on the receiver and (ii) defining the system operating conditions on overall yearly efficiency rather than design point.